Evaluación de una estrategia pedagógica para mejorar la relación docente alumno de la facultad de odontología en la Universidad Antonio Nariño sede Bucaramanga (2020)
The present research work was carried out with the aim of evaluating a pedagogical strategy applied to teachers and students at the Faculty of Dentistry of the Antonio Nariño University in Bucaramanga, in order to help re-establish the relationship around their coexistence it was carried out with an experimental study with a quasi-experimental design; as a data collection instrument, a Likert-type survey was prepared, applied before (pre) and after (post) the implementation of the pedagogical strategy. In the results it is highlighted that in the inferential statistical analysis to the survey applied to the students (pre and post) the t-student statistic resulted in a p value of 0.05, establishing a statistically significant difference; as for the results in the survey to the teachers, the t-student test between the pre and post test, obtained a p value of 0.22, which allows interpreting the Non-statistical significance of the difference. In conclusions, the relevance of this type of intervention in academic communities is highlighted, because it is shown to improve aspects of coexistence, interpersonal relations, monitoring of the norm, and respect.